2018
DOI: 10.1016/j.foodres.2018.06.008
|View full text |Cite|
|
Sign up to set email alerts
|

Selection of potential non-Sacharomyces probiotic yeasts from food origin by a step-by-step approach

Abstract: Due to healthcare is increasing in nowadays, the use of the commercial probiotics is in progress and each day they are more demanded. The challenge of this study is to identify yeast species for using as probiotic organisms. Thus, the research applied a step-by-step approach, to study the probiotic potential of non-Saccharomyces yeast strains. The 215 yeasts were isolated from different environments such as wineries, oil mills, brines cheeses, fermented vegetables and distilleries in previous works and were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 36 publications
1
22
1
1
Order By: Relevance
“…The only exceptions were the strain NCYC2321, which displayed hydrophobicity in both culture media, and strain CCY29-2-147, which showed hydrophilic properties in the minimal medium. Similar results were obtained by Rodríguez et al (2018), who noted that the M. pulcherrima strain showed rather hydrophilic properties.
Fig. 6Hydrophobic properties of yeast cells harvested from two culture media: a YPD broth, b minimal medium
…”
Section: Resultssupporting
confidence: 84%
“…The only exceptions were the strain NCYC2321, which displayed hydrophobicity in both culture media, and strain CCY29-2-147, which showed hydrophilic properties in the minimal medium. Similar results were obtained by Rodríguez et al (2018), who noted that the M. pulcherrima strain showed rather hydrophilic properties.
Fig. 6Hydrophobic properties of yeast cells harvested from two culture media: a YPD broth, b minimal medium
…”
Section: Resultssupporting
confidence: 84%
“…With the aim of identifying the strain diversity, the PCR-Random Amplification of Polymorphic DNA (RAPD) the M13 primer (5'GAGGGTGGCGGTTCT 3') (Takara Shuzo Co., Otsu, Shiga, Japan) was used. In addition, the protocol proposed by Fernandez-Pacheco et al [6] was used. After the reaction, the products were separated by electrophoresis on a 1.5% agarose gel and were visualized by the gel Green (6×) in a gel documentation system.…”
Section: Strain Levelmentioning
confidence: 99%
“…In Spain there is currently only one yeast strain marketed as a probiotic (CNCM I-745, Ultra-Levura), belonging to Saccharomyces boulardii species, although in recent years there have been numerous research studies about probiotic capability in yeasts (1)(2)(3)(4)(5)(6). These studies have shown the good probiotic potential of strains of Saccharomyces cerevisiae, Hanseniaspora osmophila, Lachancea thermotolerans, Metschnikowia ziziphicola, and Pichia kudriavzevii, among others.…”
Section: Introductionmentioning
confidence: 99%